A revision of the genus Coryssiphus Simon, 1903, with its transfer to Systariinae (Araneae: Miturgidae) - Bosselaers, Jan (Zootaxa, 2024)
The genus Coryssiphus Simon, 1903 is redescribed and found to be composed of two species. Coryssiphus unicolor Simon, 1903 is synonymised with C. cinerascens Simon, 1903, being the female of that species. Coryssiphus praeustus Simon, 1903 and C. cinerascens are redescribed and the genus is transferred from Liocranidae to Miturgidae: Systariinae based on a number of somatic and genitalic characters. The peculiar presence of Coryssiphus in Africa is briefly discussed.